Efeito da administração sistêmica de um analgésico de ação central/antinflamatório e um dessensibilizante tópico pós operatória na sensibilidade dentária induzida pelo clareamento em consultório - Araújo, Isabela Dantas Torres de (2020)
OBJECTIVE: To evaluate the effectiveness of systemic administration of paracetamol 500 mg / codeine phosphate 30 mg (PACO) associated with the topical postoperative application of a desensitizer in reducing tooth sensitivity during and after in-office toothbleaching. MATERIAL AND METHODS:A randomized, controlled, triple-blind, split-mouth clinical trial was conducted, in which 40 volunteers ingested PACO (n = 20) or placebo (n = 20) prior to the procedure, and their hemiarchies received application of topical desensitizer (Desensibilize Nano-P®-NP) and prophylactic paste (PAS), totaling four groups: PACO/NP, PACO/PAS, PLA/NP andPLA/PAS. Participants underwent two tooth bleachingsessions (35% hydrogen peroxide) with two 20-minute applications in each session, and the desensitizer/prophylactic paste was applied after the procedure for five minutes, according to the manufacturer. In sessions, medication wasadministered to participants one hour before the procedure and every six hours for 48 hours. The referred sensitivity level was obtained at each session and daily for sevendays using the millimetric Visual Analog Scale. Statistical analysis was performedfor the variables immediate global sensitivity (IGS), global sensitivity (GS) and daily sensitivity (DS) through the ANOVA tests at 1 and 2 factors followed by the Tukey post-test (p<0.05). RESULTS:For IGSand GS, there were statistically significant differences between therapeutic managements, whose PLA/PAS group showed an average of at least 2 timesgreater compared to the PACO/NP group. For DS, greater sensitivity intensity was observed on the 8th day, followed by the 1st day. CONCLUSION:In-office toothbleachingusing 35% hydrogen peroxide with systemic administration of PACO associated with the topical postoperative application of Desensibilize Nano-P®was able to reduce the level of tooth sensitivity